Implementation gaps for asthma prevention and control. (September 2017) - Tanno, Luciana K.; Haahtela, Tari; Calderon, Moises A.; Cruz, Alvaro; Demoly, Pascal; ,
Abstract: Asthma and allergic diseases can start in childhood and persist throughout life, but could also be manifested later, at any time for still misunderstood reasons. They are major chronic multifactorial respiratory diseases, for which prevention, early diagnosis and treatment is recognized as a priority for the Europe's public health policy and the United Nations. Given that allergy triggers (including infections, rapid urbanization leading to loss in biodiversity, pollution and climate changes) are not expected to change in a foreseeable future, it is imperative that steps are taken to develop, strengthen and optimize preventive and treatment strategies. Currently there are good treatments for asthma, several risk factors are known (e.g., allergies, rhinitis, tobacco smoke) and tools to control the disease have been developed. However, we are still uncertain how to prevent patients from developing asthma and allergic diseases. In this paper, we list the positive and negative experiences in this field as well as analyze the missing links in the process. This critical analysis will be the basis of setting-up an effective program for prevention and making, a process labeled as "implementation gaps".